Manipulation of Mononuclear Phagocytes by HIV: Implications for Early Transmission Events - Bertram, Kirstie Melissa; Tong, Orion; Royle, Caroline; Turville, Stuart Grant; Nasr, Najla; Cunningham, Anthony Lawrence; Harman, Andrew Nicholas (Frontiers in Immunology, 2019)
Mononuclear phagocytes are antigen presenting cells that play a key role in linking the innate and adaptive immune systems. In tissue, these consist of Langerhans cells, dendritic cells and macrophages, all of which express the key HIV entry receptors CD4 and CCR5 making them directly infectible with HIV. Mononuclear phagocytes are the first cells of the immune system to interact with invading pathogens such as HIV. Each cell type expresses a specific repertoire of pathogen binding receptors which triggers pathogen uptake and the release of innate immune cytokines. Langerhans cells and dendritic cells migrate to lymph nodes and present antigens to CD4 T cells, whereas macrophages remain tissue resident. Here we review how HIV manipulates these cells by blocking their ability to produce innate immune cytokines and taking advantage of their antigen presenting cell function in order to gain transport to its primary target cells, CD4 T cells.